2016
DOI: 10.1021/acscatal.6b01131
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydrodeoxygenation of m-Cresol over Bimetallic Pt–Mo Catalysts through an Oxophilic Metal-Induced Tautomerization Pathway

Abstract: Supported bimetallic catalysts consisting of a noble metal (e.g., Pt) and an oxophilic metal (e.g., Mo) have received considerable attention for the hydrodeoxygenation of oxygenated aromatic compounds produced from biomass fast pyrolysis. Here, we report that PtMo can catalyze m-cresol deoxygenation via a pathway involving an initial tautomerization step. In contrast, the dominant mechanism on monometallic Pt/Al2O3 was found to be sequential Pt-catalyzed ring hydrogenation followed by dehydration on the suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 89 publications
5
90
0
2
Order By: Relevance
“…It has been reported that reduced Mo 4+ sites play an important role in the adsorption of hydrogen, whereas Mo 5+ species are important for the adsorption of oxygenated substrates . In our work, we suggest that oxygen vacancies (i.e., reduced MoO x species: Mo 4+ and Mo 5+ ), where the reactants can be activated, are created primarily upon reduction . The UV/Vis spectra of fresh and reduced catalysts validate the generation of oxygen defects on the catalytic surface (Figure S6), as the relatively increased absorption in the visible region ( λ ≈400–800 nm) indicates the presence of oxygen vacancies .…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…It has been reported that reduced Mo 4+ sites play an important role in the adsorption of hydrogen, whereas Mo 5+ species are important for the adsorption of oxygenated substrates . In our work, we suggest that oxygen vacancies (i.e., reduced MoO x species: Mo 4+ and Mo 5+ ), where the reactants can be activated, are created primarily upon reduction . The UV/Vis spectra of fresh and reduced catalysts validate the generation of oxygen defects on the catalytic surface (Figure S6), as the relatively increased absorption in the visible region ( λ ≈400–800 nm) indicates the presence of oxygen vacancies .…”
Section: Resultsmentioning
confidence: 53%
“…[50] In our work, we suggest that oxygen vacancies (i.e.,r educed MoO x species:M o 4+ + and Mo 5+ + ), where the reac-tants can be activated, are created primarily upon reduction. [51] The UV/Vis spectra of fresh and reduced catalysts validate the generation of oxygen defects on the catalytic surface (Figure S6), as the relativelyi ncreased absorption in the visible region( l % 400-800 nm) indicates the presence of oxygen vacancies. [52] There are three different types of surface oxygen centers that can be reduced to create oxygen vacancies;t erminal (i.e.,l inked to one Mo atom), asymmetric bridging (i.e.,l ocated asymmetrically between two Mo atoms), and symmetric bridging (i.e.,l ocated symmetrically between two Mo atoms).…”
Section: Implications On the Reaction Mechanismmentioning
confidence: 74%
“…[36][37][38] As with the model reactants, we observed high HDO selectivity using the Pd@TiO 2 -WI ( Figure 6). [36][37][38] As with the model reactants, we observed high HDO selectivity using the Pd@TiO 2 -WI ( Figure 6).…”
mentioning
confidence: 63%
“…In a later study, the presence of Mo(V) species on the surface of the catalyst was found to act as a Lewis acid site that weakened the C-O bond upon adsorption of the molecule on the active site [25]. The influence of Mo in HDO reactions indicates that it increases the selectivity toward deoxygenated products shown by PtMo catalyst with respect to the monometallic one, where the Mo seems to introduce a new preferred pathway by changing the kinetic barriers [26]. So these studies suggest that molybdenum-based catalysts have unique properties that make them suitable for use as HDO catalysts.…”
Section: Introductionmentioning
confidence: 93%